Genotyping of colorectal cancer for cancer precision medicine: Results from the IPH Center for Molecular Pathology - Jesinghaus, Moritz; Pfarr, Nicole; Endris, Volker; Kloor, Matthias; Volckmar, Anna-Lena; Brandt, Regine; Herpel, Esther; Lasitschka, Felix; Schirmacher, Peter; Penzel, Roland; Weichert, Wilko; Stenzinger, Albrecht (Genes, chromosomes & cancer, 2016)
Cancer precision medicine has opened up new avenues for the treatment of colorectal cancer (CRC). To fully realize its potential, high-throughput sequencing platforms that allow genotyping beyond KRAS need to be implemented and require performance assessment. We comprehensively analyzed first-year data of 202 consecutive formalin-fixed paraffin embedded (FFPE) CRC samples for which prospective genotyping at our institution was requested. Deep targeted genotyping was done using a semiconductor-based sequencing platform and a self-designed panel of 30 CRC-related genes. Additionally, microsatellite status (MS) was determined. Ninety-seven percent of tumor samples were suitable for sequencing and in 88% MS could be assessed. The minimal drop-out rates of 6 and 25 cases, respectively were due to too low amounts or heavy degradation of DNA. Of 557 nonsynonymous mutations, 90 (16%) have not been described in COSMIC at the time of data query. Forty-three cases (22%) had double- or triple mutations affecting a single gene. Sixty-four percent had genetic alterations influencing oncological therapy. Eight percent of patients (MSI phenotype: 6%; mutated POLE: 2%) were potentially eligible for treatment with immune checkpoint inhibitors. Of 56% of KRASwt CRC that potentially qualified for anti-EGFR treatment, 30% presented with mutations in BRAF/NRAS. Mutated PIK3CA was detected in 21%. In conclusion, we here present real-life routine diagnostics data that not only demonstrate the robustness and feasibility of deep targeted sequencing and MS-analysis of FFPE CRC samples but also contribute to the understanding of CRC genetics. Most importantly, in more than half of the patients our approach enabled the selection of the best treatment currently available. © 2016 Wiley Periodicals, Inc.
Gesehen am 05.09.2019